Presence of Essential Hypertension or Diabetes Mellitus Is a Predictor of Intracranial Bleeding in Elderly Patients: A Study of 108 Patients with Isolated Thrombocytopenia from a Single Reference Center - Rajan Kapoor; Hara Prasad Pati; Manoranjan Mahapatra; Anuradha Monga (Turkish Journal of Hematology, 2015)
INTRODUCTION: Thrombocytopenia poses a significant problem in the elderly. Not only are there varied causes, but it is also associated with significant morbidity and mortality. We carried out a study to learn the causes of isolated thrombocytopenia in elderly patients and to correlate the severity of thrombocytopenia and bleeding manifestations with various etiologic factors and comorbidities. METHODS: A total of 108 patients above 50 years of age presenting with isolated thrombocytopenia (platelet counts of <100x109/L with normal hemoglobin and total leukocyte counts) were enrolled in the study. Detailed history and clinical examinations were carried out for each patient. Complete blood counts were analyzed by automated cell counter. Peripheral smears were examined in all cases. HbsAg, anti-HCV, and anti-HIV testing by enzyme-linked immunosorbent assay was done in all patients. Wherever clinically indicated, bone marrow aspiration biopsy and cytogenetic studies were done. RESULTS: Out of 108 patients, 102 (94.4%) presented with bleeding tendencies. Twenty-nine (26.8%) presented with serious (World Health Organization grade 3/4) bleedings. Major findings were immune thrombocytopenic purpura in 79 (73.1%), myelodysplastic syndrome in 7 (6.5%), drug-induced thrombocytopenia in 7 (6.5%), and connective tissue disorder in 4 (3.7%) cases. Ten patients presented with intracranial bleedings. Upon logistic regression analysis, comorbidities in the form of essential hypertension and diabetes mellitus were significantly associated with occurrence of intracranial bleeding. There was no correlation of serious bleedings with platelet counts. DISCUSSION AND CONCLUSION: Isolated thrombocytopenia in the elderly is associated with significant morbidity. Diligent clinical and laboratory evaluation is required to elucidate the cause of thrombocytopenia in the elderly. Comorbidities in this population are associated with serious bleedings and not low platelet counts as is commonly thought.